Immunostimulatory Endogenous Nucleic Acids Perpetuate Interface Dermatitis—Translation of Pathogenic Fundamentals Into an In Vitro Model - Braegelmann, Christine; Fetter, Tanja; Niebel, Dennis; Dietz, Lara; Bieber, Thomas; Wenzel, Joerg (Frontiers in Immunology, 2021)
Interface dermatitis is a histopathological pattern mirroring a distinct cytotoxic immune response shared by a number of clinically diverse inflammatory skin diseases amongst which lichen planus and cutaneous lupus erythematosus are considered prototypic. Interface dermatitis is characterized by pronounced cytotoxic immune cell infiltration and necroptotic keratinocytes at the dermoepidermal junction. The initial inflammatory reaction is established by cytotoxic immune cells that express CXC chemokine receptor 3 and lesional keratinocytes that produce corresponding ligands, CXC motif ligands 9/10/11, recruiting the effector cells to the site of inflammation. During the resulting anti-epithelial attack, endogenous immune complexes and nucleic acids are released from perishing keratinocytes, which are then perceived by the innate immune system as danger signals. Keratinocytes express a distinct signature of pattern recognition receptors and binding of endogenous nucleic acid motifs to these receptors results in interferon-mediated immune responses and further enhancement of CXC chemokine receptor 3 ligand production. In this perspective article, we will discuss the role of innate nucleic acid sensing as a common mechanism in the perpetuation of clinically heterogeneous diseases featuring interface dermatitis based on own data and a review of the literature. Furthermore, we will introduce a keratinocyte-specific in vitro model of interface dermatitis as follows: Stimulation of human keratinocytes with endogenous nucleic acids alone and in combination with interferon gamma leads to pronounced production of distinct cytokines, which are essential in the pathogenesis of interface dermatitis. This experimental approach bears the capability to investigate potential therapeutics in this group of diseases with unmet medical need.